Bibliometric Analysis of Digital Tax Administration - Loso Judijanto (Westscience Press, 2026)
The rapid expansion of the digital economy has encouraged governments worldwide to modernize taxation systems through digital tax administration. This study aims to map the intellectual structure, research trends, and collaboration patterns within the field of digital tax administration using a bibliometric approach. Data were collected from the Scopus database and analyzed using VOSviewer to generate network, overlay, and density visualizations, as well as co-authorship, institutional, and country collaboration analyses. The findings reveal that taxation, tax administration, and the digital economy form the core themes of the literature, reflecting a strong integration between fiscal policy and digital governance. Recent research trends show increasing attention toward emerging technologies such as artificial intelligence, blockchain, and big data, indicating a shift toward innovation-driven tax systems. Collaboration patterns highlight the dominant contributions of several countries and institutions, while emerging economies are gradually expanding their presence in the field. The results suggest that digital tax administration research is evolving toward a technology-oriented and globally interconnected paradigm, emphasizing efficiency, transparency, and sustainable governance in modern taxation systems.